2019
DOI: 10.3390/vaccines7040198
|View full text |Cite
|
Sign up to set email alerts
|

Palm Tocotrienol-Adjuvanted Dendritic Cells Decrease Expression of the SATB1 Gene in Murine Breast Cancer Cells and Tissues

Abstract: The aim of this study was to evaluate the effectiveness of immunotherapy using dendritic cells (DC) pulsed with tumor lysate (a DC vaccine) in combination with daily supplementation of tocotrienol-rich fraction (TRF) to potentiate anti-tumor immune responses. We had previously reported that DC-vaccine immunotherapy together with TRF supplementation induced protective immunity to tumor challenge. Breast cancer was induced in female BALB/c mice. The mice were randomly assigned into the treatment groups. At autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Hence, short term feeding of γT3 once tumour is palpable, may be insufficient to prepare the host immune system to control the tumour. Previous studies that have looked at effects of TRF supplementation in tumourinduced mice vaccinated with dendritic cell (DC) vaccines before (Abdul Hafid and Radhakrishnan, 2019;Abdul Hafid et al, 2013;Hafid et al, 2010) showed enhanced immune function and tumour suppression. However, it should be noted that in both these studies, the animals were supplemented with TRF for a longer period, which may have been sufficient to regulate the host immune system to fight against cancer.…”
Section: P R E S Smentioning
confidence: 99%
“…Hence, short term feeding of γT3 once tumour is palpable, may be insufficient to prepare the host immune system to control the tumour. Previous studies that have looked at effects of TRF supplementation in tumourinduced mice vaccinated with dendritic cell (DC) vaccines before (Abdul Hafid and Radhakrishnan, 2019;Abdul Hafid et al, 2013;Hafid et al, 2010) showed enhanced immune function and tumour suppression. However, it should be noted that in both these studies, the animals were supplemented with TRF for a longer period, which may have been sufficient to regulate the host immune system to fight against cancer.…”
Section: P R E S Smentioning
confidence: 99%
“…Tocotrienol (T3), a major component of vitamin E from palm oil, has unique antioxidant and antiinflammatory properties [9], which are beneficial in inflammation-associated diseases [10]. Several studies have shown that T3 acts as a potent inducer of apoptosis in many cancer cells [11,12,13]; possess immune regulatory roles, which reduces the risk of respiratory infections and allergy [14,15]; confer protection against oxidative stress [16,17]as well as cardiovascular [15] and neurodegenerative [17] diseases. Therefore, this study aimed to evaluate how T3 cause anti-inflammatory responses using a cellbased inflammation model, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these approaches might help curb the alarming rise in BC cases. Tocotrienol rich-fraction (TRF) is a naturally occurring form of vitamin E, which has been reported to induce apoptosis in various cancer cells in cell-based and animal studies (Abdul-Hafid et al, 2019;Aggarwal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Tocotrienols are considered more potent than tocopherols and are promising anticancer agents due to their potent effects against many cancers (Ling et al, 2012). Several cell-based and animal model studies have shown that palm TRF possessed antitumour properties in prostate, breast, skin, colon, stomach, pancreatic, liver and lung cancers through apoptosis, anti-angiogenesis, anti-proliferative and immunoregulation (Parveez et al, 2019;Abdul-Hafid et al, 2019;Aggarwal et al, 2019). Studies conducted by researchers showed that tocotrienols possessed several anticancer properties that made them superior to tocopherols (Ling et al, 2012;Wong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%